Comparison of older and younger patients with ovarian cancer: A post hoc study (JGOG3016‐A3) of the treatment strength and prognostic outcomes of conventional or dose‐dense chemotherapy. Issue 5 (1st March 2023) - Itani, Yoshio; Sakai, Hitomi; Hamano, Tetsutaro; Asai‐Sato, Mikiko; Futagami, Masayuki; Fujimura, Masaki; Aoki, Yoichi; Suzuki, Nao; Yoshida, Yoshio; Enomoto, Takayuki
Abstract: Aim: To evaluate changes of treatment strength and its impact on prognosis in older patients with ovarian cancer. Methods: We compared relative dose intensity (RDI) as a representative of treatment strength, prognosis, and other features between older (≥65 years) and younger patients (<65 years) retrospectively. Seventy‐seven older patients of 301 who received dose‐dense‐paclitaxel‐carboplatin (dTC) and 93 older patients of 304 who received conventional‐paclitaxel‐carboplatin (cTC) from the Japanese Gynecologic Oncology Group (JGOG) 3016 clinical trial were analyzed. Results: The RDI of older patients was lower than that of younger patients in cTC (87.4% vs. 90.8%, p  = 0.009) but not in dTC (79.0% vs. 81.2%, p  = 0.205). In both regimens, older patients had worse overall survival than younger patients: hazard ratio [HR] = 1.80; 95% confidence interval [CI]: 1.25–2.59; p  = 0.001 for dTC, and HR = 1.59; 95% CI: 1.15–2.19; p  = 0.04 for cTC. However, the RDI was not determined as a prognostic factor statistically. The prognostic factors identified by multivariate analysis for both regimens were clinical stage and residual disease; for dTC were age, performance status, and serum albumin; and for cTC was white blood cell count. There was no difference in neutropenia observed between age groups in either regimen. Conclusions: The RDI of older patients varies according to the administered schedule and is not always lower than that of younger patients. Older patients with comparable treatment strength to younger patients in the dTC group did not accomplish the same level of prognosis as younger patients. Other biologic factors attributable to aging may affect prognosis.